1492. Targeted Substitution of Omadacycline in Place of Standard of Care for CABP Treatment is Associated with a Risk Reduction of Clostridioides difficile Infection and Financial Cost Savings in the Acute Care Setting. (31st December 2020) - Rodriguez, Mauricio; Chitra, Surya; Wright, Kelly; Lodise, Thomas
Abstract: Background: Real-world evidence studies indicate that around 3% of hospitalized patients with community-acquired pneumonia (CAP) develop Clostridioides difficile infection (CDI; Chalmers et al, J Infect 2016;73:45–53). Factors associated with increased CDI risk include Davis risk score (DRS) ≥ 6, and treatment with high-risk antibiotics such as fluroquinolones (FQ) and ceftriaxone (CTX). Omadacycline (OMC) is indicated for the treatment of community-acquired bacterial pneumonia (CABP) and has demonstrated a low propensity to induce CDI in preclinical and clinical studies. In the phase 3 OPTIC study, 2% of CABP patients who received moxifloxacin (MOX) developed CDI vs 0% for OMC (Stets et al, N Engl J Med 2019;380:517–27); 14% of MOX patients with DRS ≥ 6 developed CDI vs 0% in the OMC group (Table 1; Figure 1 ). We assessed the economic impact of substituting current CABP treatment (FQ and CTX) with OMC for hospitalized CABP patients with DRS ≥ 6. Table 1 Figure 1 Methods: A deterministic healthcare-decision analytic model was performed. Only excess costs associated with each treatment were considered. Base-case model inputs were: yearly CAP admission in US, prevalence of CAP patients with DRS ≥ 6, CDI risk for CAP patients with DRS ≥ 6 with current CABP treatments, CDI costs (initial and recurrent), and OMC cost (Table 2 ). Efficacy and safety of treatments were assumed to be equal. CDI risk of 0% was assumed for OMC. Costs are reported as USD. Table 2 Results: For patients with CABP, total CDI costs were $738M, with first-episode costs of $489M plus recurrence costs of $249M. The cost of 5 days (mean hospital length of stay for CABP) of OMC was $207M. Use of OMC for the estimated 100, 000 CABP patients with DRS ≥ 6 would result in a potential cost saving of up to $531M for this patient population, assuming CDI risk of 0% with OMC. As CDI is a risk from any antibiotic use, cost savings can be achieved when OMC is used in place of high-risk antibiotics patients when CDI risk rates exceed 3.9%. Conclusion: Our findings suggest prioritizing use of omadacycline over current CABP treatments in hospitalized CABP with a DRS ≥ 6 may substantially reduce attributable CDI costs. These results can serve as a basis for stewardship interventions to reduce hospital CDI rates and associated costs. Disclosures: Mauricio Rodriguez, PharmD, BCPS, BCCCP, BCIDP, Paratek Pharmaceuticals, Inc. (Employee) Surya Chitra, PhD, Paratek Pharmaceuticals, Inc. (Consultant) Kelly Wright, PharmD, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Thomas Lodise, PharmD, PhD, Paratek Pharmaceuticals, Inc. (Consultant)